Identifying variable γ-ray sources through radio observations - Paredes, Josep M. (2005)
We present preliminary results of a campaign undertaken with different radio interferometers to observe a sample of the most variable unidentified EGRET sources. We expect to detect which of the possible counterparts of the γ-ray sources (any of the radio emitters in the field) varies in time with similar timescales as the γ-ray variation. If the γ-rays are produced in a jet-like source, as we have modelled theoretically, synchrotron emission is also expected at radio wavelengths. Such radio emission should appear variable in time and correlated with the γ-ray variability.